STUDY OF COAL DUST CONCENTRATION 74-53𝝁m AND 53-44 μm ON EXPLOSION PRESSURE OF COAL USING 20 LITER EXPLOSION CHAMBER ON LABORATORY SCALE - Gassadesna Arisandi (NIM : 12114033), Alan
Coal have a very important role in providing energy source all over the world. In the mining process, thereÃ‚Â’s some main problem that frequently occurs, one of them is coal dust explosion which often cause casualties. In Indonesia, thereÃ‚Â’s still a very few number of research about coal explosibility, therefore it is needed to conduct research for comparing the result with Indonesian coal characteristics. This research uses 20-Litre explosion chamber. From the acquired data, analysis is performed to obtain the desired output. First is analysis concerning effect of concentration change to explosion pressure generated, with intention of finding the coalÃ‚Â’s saturated concentration. Second is analysis on effect of difference in coal dust particle size to explosion pressure generated, with intention to compare the coal sample with different parameter for referencing. Last is dettermination of maximum energy generated during test, with intention to predict the power and impact of explosion. From the experiment, we obtain highest Maximum pressure at concentration 600 g/m3using 53-44μm coal dust sample and highest Maximum rate of pressure rise at concentration 1000 g/m3 using 53-44μm coal dust sample.